Phenotype–genotype spectrum of AAA syndrome from Western India and systematic review of literature. Issue 8 (November 2017) - Patt, Hiren; Koehler, Katrin; Lodha, Sailesh; Jadhav, Swati; Yerawar, Chaitanya; Huebner, Angela; Thakkar, Kunal; Arya, Sneha; Nair, Sandhya; Goroshi, Manjunath; Ganesh, Hosahithlu; Sarathi, Vijaya; et al.
Abstract : Objective: To study genotype–phenotype spectrum of triple A syndrome (TAS). Methods: Retrospective chart analysis of Indian TAS patients (cohort 1, n  = 8) and review of genotyped TAS cases reported in world literature (cohort 2, n  = 133, 68 publications). Results: Median age at presentation was 4.75 years (range: 4–10) and 5 years (range: 1–42) for cohorts 1 and 2, respectively. Alacrima, adrenal insufficiency (AI), achalasia and neurological dysfunction (ND) were seen in 8/8, 8/8, 7/8 and 4/8 patients in cohort 1, and in 99, 91, 93 and 79% patients in cohort 2, respectively. In both cohorts, alacrima was present since birth while AI and achalasia manifested before ND. Mineralocorticoid deficiency (MC) was uncommon (absent in cohort 1, 12.5% in cohort 2). In cohort 1, splice-site mutation in exon 1 (p.G14Vfs*45) was commonest, followed by a deletion in exon 8 (p.S255Vfs*36). Out of 65 mutations in cohort 2, 14 were recurrent and five exhibited regional clustering. AI was more prevalent, more often a presenting feature, and was diagnosed at younger age in T group (those with truncating mutations) as compared to NT (non-truncating mutations) group. ND was more prevalent, more common a presenting feature, with later age at onset in NT as compared to T group. Conclusion: Clinical profile of our patients is similar to that of patients worldwide. Alacrima is the earliest and most consistent finding. MC deficiency is uncommon. Some recurrent mutations show regional clustering. p.G14Vfs*45 and p.S255Vfs*36 account for majority of AAAS mutations in our cohort. Phenotype of T group differs from that of NT group and merits future research.